Performance Analysis of Micro-Hydro Plants Using Crossflow Turbines at Varying Water Fall Heights - Wardhany, Arum Kusuma; Monika, Dezetty; Ariansyah, Rafi; Lubis, Muhammad Rasyid; Arifin, Muhammad; Aji, A. Damar (Emitor: Jurnal Teknik Elektro, 2025)
Hydropower plants have limitations in scalability and location, as they require large water flows and complex infrastructure. One solution to overcome these drawbacks is portable hydroelectric power plants, which are more flexible and adaptable to variations in water level. Portable geothermal power plants allow the regulation of water fall height to optimise their performance, especially in remote areas that are not reached by conventional power grids. This research aims to develop the performance of portable geothermal power plants by utilising variations in water level to analyse the performance of the effect of water fall height on the performance of portable geothermal power plants with crossflow turbines. This research uses an experimental method, which involves collecting and analysing data from the height of (variation 1) and (variation 2) to determine the performance of the Pico Hydro Power Plant (PLTPh). The research was conducted at Mahogany Lake, University of Indonesia. The data collected includes measurements of voltage, current, power, and rotation speed of the turbine and generator at different altitude variations to determine the effect of water fall height on the performance of PLTPh with crossflow turbines. The results showed that the height of the water fall can affect the performance of the Pico Hydro Power Plant (PLTPh). At the height (variation 1), the power and output voltage generated are higher than the height (variation 2). In addition, the output voltage is also greater when the generator is operating without load. This difference shows that variations in altitude, flow speed and water discharge entering the turbine cross section greatly affect the rotation of the generator and the amount of electrical power generated by the PLTPh.